ACEITAÇÃO E USO DE TECNOLOGIAS NO SERVIÇO PÚBLICO: UMA ANÁLISE DAS ATIVIDADES PEDAGÓGICAS NÃO PRESENCIAIS (APNP´s) EM UMA INSTITUIÇÃO DE ENSINO FEDERAL - Francischeto, Bruno Tardin (2022)
With the introduction of information technology in the business environment as a method to increase labor productivity, researchers realized studies under several approaches resulting in models and theories of acceptance and use of technologies by the users, based on psychosocial constructs and their interrelationships. The Covid-19 pandemic made governments adopt lockdowns as a manner of containing and controlling the virus spread. In this way, Ifes by means of its Superior Council approved resolution migrating face-to-face teaching to distance learning, where every pedagogical activity by the scholastic must be mandatorily realized through the institutional platform AVA- Cefor Moodle-Ifes. The urgency of the moment has not allowed Ifes to analyze the group of psychosocial factors and their interrelationships that affect the purpose of use and the behavior of use of the new users of AVA-Cefor Moodle-Ifes, but the new environment provided wide opportunities for the realization of researches in the field of acceptance and use of technologies. In this way, the proposed research issue is: What are and how the previous psychosocial constructs relate to the acceptance and the use os APNPs in a federal educational institution? This project seeking to analyze the feasibility and reliability of the constructs in the adapted model, verifying the predictive capacity of the model.The theoretical contribution brings up the acceptance and use of technologies, with the use of Unified theory of acceptance and use of technology, UTAUT, where is proposed an adapted model with the inclusion of the Social Isolation construct in the pandemic context. The dissertation project classifies: As for the approach of the issue, as to the quantitative character, since it plans to perform the analysis of variables by the means of Modeling structural equations by partial least squares (PLS-SEM); As for the ends, as descriptive for perform a construct description and their interrelationships in the acceptance and use of Moodle as an e-learning tool; As for the procedures, such as Survey research adapted to the UTAUT model; As for the method, the project leans of the deductive-hypothetical approach. The data source of the study will be all Ifes’ teachers. From the research results, as the expected technological outgrowth, it is proposed to submit a report of research containing the diagnostic data, with possible improvement suggestions to the institution in a possible post-pandemic scenario.